Comparison of two new integrated SS-OCT tomography and biometry devices. Issue 11 (November 2022) - Sorkin, Nir; Achiron, Asaf; Abumanhal, Muhammad; Abulafia, Adi; Cohen, Eyal; Gutfreund, Shay; Mandelblum, Jorge; Varssano, David; Levinger, Eliya
Abstract : A comparison of two new integrated SS-OCT tomography/biometry devices (the Eyestar 900 and Anterion) showed good agreement in biometry measurements and IOL power calculation. Corneal diameter measurements had reduced agreement. Abstract : Purpose: To evaluate the agreement in biometry measurements and intraocular lens (IOL) power calculations between 2 integrated swept-source optical coherence tomography (SS-OCT) tomography/biometry devices: the Eyestar 900 and the Anterion. Setting: Tel Aviv Medical Center, Tel Aviv, Israel. Design: Retrospective comparative study. Methods: 113 eyes of 66 consecutive patients who were evaluated prior to cataract surgery using both devices on the same visit were included. Measurements of axial length, anterior and posterior keratometry, anterior chamber depth, corneal diameter (CD), central corneal thickness, and lens thickness were recorded from both devices and analyzed for agreement and correlation. IOL power calculations using Barrett Universal II formula were compared between the devices in addition to prediction error (PE) and the mean absolute error (MAE). Results: The mean age was 71.6 ± 9.8 years. Clinically, the mean differences in measured variables were small. Measurement correlation and agreement between the devices were excellent for all variables, except for CD (Spearman r = 0.763, P < .001, and Bland-Altman 95% limits of agreement −0.21 to +0.65 mm). Good agreement was found between the devices in IOL power calculations, PE, and MAE, and the agreement was better when using the Eyestar 900 reflective keratometry measurements than the Eyestar 900 SS-OCT keratometry measurements (IOL power agreement within ±0.5 diopter (D) in 90.5% [n = 95] and 81.0% [n = 85], respectively [ P = .076], and within ±0.25 D in 64.8% [n = 68] and 44.8% [n = 47], respectively [ P = .005]). Conclusions: The 2 integrated SS-OCT tomography/biometry devices had good agreement in biometry measurements and IOL power calculations. Agreement was better when the Eyestar 900 reflective anterior keratometry measurements were used rather than the Eyestar 900 SS-OCT anterior keratometry measurements. Measurements of CD had reduced agreement and were not interchangeable.